The impact of trade relations on the prosperity of the economic activity of the ports of Central Morocco (Century 5-7 A.H./11-13 A.D.) - Hammadi, Lateef J.; Saleh, Othman A. (Al-Adab Journal, 2022)
Economic activity is the backbone of life and the basis for the establishment and continuity of states, as it is the main guide for them, and through which their position is measured, and given the important role played by this aspect in the emergence and development of the ports of Central Morocco, this study came tagged with the impact of trade relations on the prosperity of the economic activity of the ports of Central Morocco during the period (Q. 5-7 AH/11-13 AD), which includes two sections, the first section dealt with trade relations with the countries of the Islamic world, in addition to talking about the most important commodities and merchandise exchanged between the ports of the Middle Maghreb and Islamic countries, while the second topic dealt with the talk about trade relations with European countries.The importance of the issue lies in the fact that trade exchange greatly contributed to the emergence of economic activity in the ports of Central Morocco, which in turn was reflected in the general public or at the level of existing countries as a result of obtaining funds through the imposition of duties and taxes on goods and merchandise, and all other business that takes place on the land of the port, which led to the emergence of population centers and the establishment of commercial cities filled with imported goods, as well as what is rich in agricultural products, local industries and minerals. For this reason, it became a destination for merchants from everywhere, whether they were Muslims or non-Muslims, such as the merchants of Andalusia, Egypt, the Levant, Iraq, the Island, Yemen and India, as well as the countries of the northern Mediterranean from the countries of Europe.